Esas no son mis orejas (Ciencia para los más chicos : Sueños curiosos, 2004)
Follow Lola as her dreams take you to the jungle, desert, forest and swamp. She meets many different animals along the way and notices the difference in their ears. She awakes to discover the virtures of the human ear